2010
DOI: 10.1111/j.1744-7909.2010.00923.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcium at the Cell Wall‐Cytoplast Interface

Abstract: Attention is given to the role of Ca 2+ at the interface between the cell wall and the cytoplast, especially as seen in pollen tubes. While the cytoplasm directs the synthesis and deposition of the wall, it is less well appreciated that the wall exerts considerable self control and influences activities of the cytoplasm. Ca 2+ participates as a crucial factor in this two way communication. In the cytoplasm, a [Ca 2+ ] above 0.1 μM, regulates myriad processes, including secretion of cell wall components. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
96
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(102 citation statements)
references
References 125 publications
4
96
0
2
Order By: Relevance
“…Studies based on chemical and genetically encoded reporters showed that tip-focused cytosolic calcium ([Ca 2+ ] cyt ) and proton (H + ) gradients direct pollen tube growth (Pierson et al, 1994;Feijó et al, 1999;Michard et al, 2008). These cytosolic ion gradients are in line with the amplitude and direction of extracellular Ca 2+ fluxes and H + fluxes and it is generally accepted that the cytosolic gradients are, to a great extent, a consequence of local plasma membrane ion fluxes (Michard et al, 2009;Hepler and Winship, 2010). Protons enter the pollen tube tip via a yet unknown transport system, but a pronounced H + efflux is maintained behind the subapical region .…”
Section: Introductionmentioning
confidence: 81%
“…Studies based on chemical and genetically encoded reporters showed that tip-focused cytosolic calcium ([Ca 2+ ] cyt ) and proton (H + ) gradients direct pollen tube growth (Pierson et al, 1994;Feijó et al, 1999;Michard et al, 2008). These cytosolic ion gradients are in line with the amplitude and direction of extracellular Ca 2+ fluxes and H + fluxes and it is generally accepted that the cytosolic gradients are, to a great extent, a consequence of local plasma membrane ion fluxes (Michard et al, 2009;Hepler and Winship, 2010). Protons enter the pollen tube tip via a yet unknown transport system, but a pronounced H + efflux is maintained behind the subapical region .…”
Section: Introductionmentioning
confidence: 81%
“…These ions are taken up by germinating pollen grains and growing pollen tubes forming a specific tip-to-base Ca 2+ gradient. Elevated levels of Ca 2+ at the tube tip are involved in vesicle secretion and in determining the orientation of the tube growth (see the review by Ge et al 2007; Hepler and Winship 2010). Similarly, in gymnosperms, Ca 2+ is taken up by growing pollen tubes (Lazzaro et al 2005; Chen et al 2009), and as Wu et al (2008) found, the Ca 2+ influx in Pinus bungeana is even higher than in angiosperm pollen tubes.…”
Section: Introductionmentioning
confidence: 99%
“…Within the apoplast, the majority of Ca 2+ binds to negatively charged carboxylic groups of galacturonic acids (pectin) and oxalates (Sattelmacher, 2001), with the residual Ca 2+ remaining free in the apoplast for signaling functions (Hirschi, 2004). Pectate cross-linking by Ca 2+ within the cell wall affords greater strength, but little is known about the role of Ca 2+ signaling in regulating cell wall extensibility (Hepler and Winship, 2010). Apoplastic Ca 2+ is also taken up by cells where it fulfills roles in intracellular signaling, but as Ca 2+ is relatively immobile in the cell and is not transported in the phloem, it is not normally redistributed following deposition in leaf vacuoles (Clarkson, 1984;Leigh, 1997;White and Broadley, 2003).…”
Section: Introductionmentioning
confidence: 99%